2022
DOI: 10.1002/adfm.202204881
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Vacancy‐Rich La0.5Sr1.5Ni0.9Cu0.1O4–δ as a High‐Performance Bifunctional Catalyst for Symmetric Ammonia Electrolyzer

Abstract: In this study, strontium and copper dual-doped La 2 NiO 4 annealed in Ar (La 0.5 Sr 1.5 Ni 0.9 Cu 0.1 O 4-δ -Ar, LSNC-Ar) with K 2 NiF 4 structure is strategically designed as an ammonia oxidation reaction (AOR) and hydrogen evolution reaction (HER) bifunctional catalyst for high-efficiency ammonia electrolysis. The selective substitution of lanthanum with high content strontium improves the electronic conductivity and increases the oxygen vacancy concentration. Doping of Cu into the B-site of the perovskite i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 89 publications
1
18
0
Order By: Relevance
“…40 In the past five years, a wide variety of materials based on non-precious 3d transition metals, such as Ni, Cu, Co, Fe, have gained rapid recognition over Pt as an attempt to increase the practicality of AOR catalysts by lowering the cost. 11,[41][42][43][44][45][46][47] Amongst these metals, experimental studies have reported that Ni-based materials are the most promising catalysts with respect to AOR activity and high selectivity towards N 2 in low to intermediate temperature ranges. 45,48,49 However, compared to Pt, the d band center of the Ni metal is relatively wide, which means that Ni binds less strongly to the reactants and does not adsorb the reactants as efficiently as Pt.…”
Section: Overall Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 In the past five years, a wide variety of materials based on non-precious 3d transition metals, such as Ni, Cu, Co, Fe, have gained rapid recognition over Pt as an attempt to increase the practicality of AOR catalysts by lowering the cost. 11,[41][42][43][44][45][46][47] Amongst these metals, experimental studies have reported that Ni-based materials are the most promising catalysts with respect to AOR activity and high selectivity towards N 2 in low to intermediate temperature ranges. 45,48,49 However, compared to Pt, the d band center of the Ni metal is relatively wide, which means that Ni binds less strongly to the reactants and does not adsorb the reactants as efficiently as Pt.…”
Section: Overall Reactionmentioning
confidence: 99%
“…5,10 Ammonia can be dissolved in water to create a solution with a solubility limit of around 35 wt% that can be kept in a glass container without the need for any extra equipment. 2,11 In addition, it also can be readily liquified by increasing pressure to ~10 bar at room temperature or by cooling to -33 °C at atmospheric pressure, which is much easier than that of hydrogen. 5 Except for liquid storage, ammonia is found to be stored as a solid in metal-amine complexes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the increased pH of electrolytes will reduce the concentration of H + and slow down the formation of M*–H ads . However, the much higher concentration of KOH will also provide a fast mass transfer and charge transport to reduce the energy demands for the HER in the alkaline system. , …”
Section: Resultsmentioning
confidence: 99%
“…41 However, the much higher concentration of KOH will also provide a fast mass transfer and charge transport to reduce the energy demands for the HER in the alkaline system. 42,43 Compared the above electrochemical parameters with the structural characterizations, the contradiction between S BET and EASA can be attributed to the following reasons: the homogeneously distributed precursors and weak interactions of HAs@MoS 2 /Ce 2 S 3 deliver outstanding electroactive sites by reducing the aggregation; 23,37 the heterostructures of HAs@ MoS 2 /Ce 2 S 3 also provide numerous high-active catalytic sites by fabricating the edge S−M−S sites of MoS 2 , 2,5,10 the undercoordinated surface cations, and the ligand (S adsorbing H atoms to form S−H bands) number of Ce 2 S 3 . 11,12 The changes of the catalyst (HAs@MoS 2 /Ce 2 S 3 /CC) between and after the electrochemical catalysis have been further investigated.…”
mentioning
confidence: 99%
“…An X-ray photoelectron spectroscopy analyzer was used to analyze the valence state and composition of the elements of the material, and the spectra obtained were corrected by the C 1s spectral line with a binding energy of 284.8 eV (ESCALAB 250Xi, Thermo). Iodometric titration was used to test the oxygen vacancy content of perovskite oxides . Excess KI (∼2 g) and 50 mg perovskite oxides were dissolved in 100 mL of 1 M HCl.…”
Section: Experimental Partmentioning
confidence: 99%